Acceptance, Behavioral Intention, and Usage among Clients of a Government Office on Mobile Payment Services - Lagunday, Eriz Jireh B.; Menes, Carmen C. (Technium Social Sciences Journal, 2025)
Mobile payment services (MPS) have revolutionized the banking sector, providing consumers with a convenient and secure method for conducting financial transactions. This shift towards digital finance is evident globally. The ASEAN region has also experienced a significant transformation in consumer behavior and retail landscapes due to mobile payment adoption. In the Philippines, MPS holds immense potential for promoting financial inclusion. However, despite this potential, mobile payment usage remains low compared to other ASEAN nations. this study aimed to assess the level of acceptance, behavioral intention, and usage of MPS among clients of a government office in a rural municipality in Southern Negros. Specifically, it investigated the relationships between acceptance and usage of MPS, behavioral intention and usage of MPS, and usage and behavioral intention. This study employed a descriptive-correlational research design with the randomly sampled 528 clients of a government office. This study utilized an adapted and modified questionnaire tailored to investigate mobile payment usage and acceptance among taxpayers in a rural municipality in the Philippines. While drawing inspiration from the Unified Theory of Acceptance and Use of Technology (UTAUT) model, the questionnaire was adapted to address the unique context of this research. The collected data were subjected to both descriptive and correlational analyses using mean, standard deviation, frequency count, and percentage distribution. Meanwhile, correlational analysis using Shapiro-Wilk tests was employed to investigate the relationships among acceptance, behavioral intention, and actual usage. Results revealed very high acceptance and intention levels with varied usage patterns. Individual taxpayers scored higher than businesses across measures. Strong positive correlations existed between acceptance, intention, and usage. Performance Expectancy ranked highest among factors. Despite similar acceptance levels, individual taxpayers used MPS significantly more than businesses.